2017
DOI: 10.3892/etm.2017.5078
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sevoflurane on myocardial ischemia-reperfusion injury in rat hearts and its impact on HIF-1α and caspase-3 expression

Abstract: This study was designed to investigate possible protective effects of sevoflurane on myocardial ischemia-reperfusion injury (MIRI) and its impact on expression of HIF-1α and caspase-3 in rats, so as to provide new insights for the treatment of MIRI. Forty SD rats were randomly divided into four groups (n=10) including Sham operation (Sham), ischemia-reperfusion (IR), sevoflurane preconditioning group (Sevo-Pre) and sevoflurane post-conditioning (Sevo-Post) groups. Perfusion was performed using ex vivo heart pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Sev is a volatile anesthetic widely used in clinical practice. Although the efficacy and safety of Sev across the patient populations have been demonstrated and some reports have suggested that it may also have protective effects in other organs 28,29 and a large number of studies and epidemiological investigations during the past two decades have demonstrated that general anesthesia (including exposure to Sev) could be a potential risk factor for the development of cognitive dysfunctions, such as AD and POCD, especially in old people. 7,8,[30][31][32] However, the precise molecular mechanism of cognitive dysfunction induced by Sev is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sev is a volatile anesthetic widely used in clinical practice. Although the efficacy and safety of Sev across the patient populations have been demonstrated and some reports have suggested that it may also have protective effects in other organs 28,29 and a large number of studies and epidemiological investigations during the past two decades have demonstrated that general anesthesia (including exposure to Sev) could be a potential risk factor for the development of cognitive dysfunctions, such as AD and POCD, especially in old people. 7,8,[30][31][32] However, the precise molecular mechanism of cognitive dysfunction induced by Sev is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Specific adenosine receptor agonists such as neladenoson (ADORA1 agonist) or regadenoson (ADORA2A agonist) are undergoing clinical trials to better understand the effect they may have in organ protection. Interestingly, sevoflurane (fluoromethyl hexafluoroisopropyl ether), an inhalation anesthetic, which is commonly used in clinical practice, has been reported to have preconditioning effects mediated by an increase in HIF1A and a decrease in caspase-3 99 . Preconditioning by sevoflurane is currently undergoing trials for its effect on cardiac IRI protection.…”
Section: Potential Targets For Therapeutic Interventionmentioning
confidence: 99%
“…Our study demonstrates that the SEV preconditioning in a pig LTx model exhibits significant protective effects against IRI by means of anti-inflammatory effects. Although in a rat in-vivo model of SEV pre- and postconditioning it has been shown that both strategies provided significant protection against myocardial IRI [ 39 ], it is possible that a preischemic conditioning approach may be more applicable to the setting of lung IRI. Indeed, from a practical point of view, we think that the feasibility of a short application of SEV in the organ donor would be more easily applicable in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%